Association Between Indefinite Dysplasia and Advanced Neoplasia in Patients With Inflammatory Bowel Diseases Undergoing Surveillance - Mahmoud, Remi (Clin Gastroenterol Hepatol, 2019)
BACKGROUND AND AIMS: Little is known about the clinical significance of indefinite dysplasia (IND) in patients with inflammatory bowel diseases (IBD) undergoing colonoscopic surveillance for colorectal neoplasia. METHODS: We conducted a retrospective cohort analysis of 492 patients with colonic IBD for 8 or more years or concomitant primary sclerosing cholangitis, with no history of advanced colorectal neoplasia (high-grade dysplasia or colorectal cancer) or colectomy, undergoing colorectal neoplasia surveillance at tertiary IBD referral center from 2001 through 2017. Subjects received consistent histopathologic grading of dysplasia. We collected data on time to development of (advanced) colorectal neoplasia or colectomy using Kaplan Meier methods. We identified factors independently associated with (advanced) colorectal neoplasia with multivariable Cox regression analysis. RESULTS: After 2149 person-years of follow-up, 53 patients (10.8%) received a diagnosis of IND without prior or synchronous low-grade dysplasia (LGD). Compared to patients without dysplasia, patients with IND had a significantly higher risk of advanced colorectal neoplasia (adjusted hazard ratio, 6.85; 95% CI, 1.78–26.4) and colorectal neoplasia (adjusted hazard ratio, 3.25; 95% CI, 1.50–7.05), but not colectomy (P=.78). Compared to IND, LGD was associated with a significantly higher risk of advanced colorectal neoplasia (P=.05). Following a diagnosis of no dysplasia, IND only, or LGD, the incidence rates of advanced colorectal neoplasia were 0.4% per patient-year, 3.1% per patient-year, and 8.4% per patient-year, respectively. CONCLUSIONS: In a retrospective analysis of patients with IBD undergoing colorectal neoplasia surveillance with consistent histopathologic grading of dysplasia, IND was independently associated with a significant increase in risk of advanced colorectal neoplasia. These findings require validation and if confirmed, a reappraisal of the colorectal neoplasia surveillance guidelines.